Music, power and liberty : sound, song and melody as instruments of change / (Acc. D2134) - Urbain, Olivier (London : I.B. Tauris, 2016)
Music is a complex and multi-faceted art form. Yet too often it is regarded as discrete and self-contained. The chapters in this groundbreaking book explore different aspects of how music may shape society and culture, yet go much further in viewing musical activity as a mode of power that can transform the lives of communities and individuals. The contributors (who include sociologists, musicologists and performers) focus above all on the relationship between music and the political upheavals of the Arab Spring. They examine key topics like music and revolution in Tunisia; the Egyptian musical tradition of the Revolutionary Song; and the ambivalent social status of the Arab musician, revered by the public when performing but also facing suspicion in a society where music is rightly seen as dangerous and subversive. In showing how music has been used to challenge the status quo, as well as enforce it, the ambiguity of music is fully revealed: it can be used to bolster both regime power and popular liberty, often simultaneously. This is a vital contribution to more nuanced understandings of music and politics.